Information technology and gender economic inclusion in sub-Saharan Africa - Simplice Asongu; Joseph Amankwah Amoah; Rexon T. Nting; Godfred Adjapong Afrifa (African Governance and Development Institute (AGDI), 2020)
This study investigates how ICT affects gender economic inclusion via gender parity education channels. We examine the issue using data from 49 countries in sub-Saharan Africa for the period 2004-2018 divided into: (i) 42 countries for the period 2004-2014; and (ii) 49 countries for the period 2008-2018. Given the overwhelming evidence of negative net effects in the first sample, an extended analysis is used to establish thresholds of ICT penetration that nullify the established net negative effects. We found that in order to enhance female labor force participation, the following ICT thresholds are worthwhile for the secondary education channel: 165 mobile phone penetration per 100 people, 21.471 internet penetration per 100 people and 3.475 fixed broadband subscriptions per 100 people. For the same outcome of inducing a positive effect on female labor force participation, a 31.966 internet penetration per 100 people threshold, is required for the mechanism of tertiary school education. These computed thresholds have economic meaning and policy relevance because they are within the established ICT policy ranges. In the second sample, a mobile phone penetration threshold of 122.20 per 100 people is needed for the tertiary education channel to positively affect female labor force participation.
Keywords: G20; I10; I32; O40; O55; 330; Africa; ICT; Gender; Inclusive development